2018
DOI: 10.3906/fiz-1707-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of various reflector elements material types on the core nuclear parameters of the 2 MW Triga Mark-II research reactor using the Monte Carlo code

Abstract: The influence of variation in the kind of material of neutron reflector elements on the core neutronic parameters of the Moroccan Triga Mark-II research reactor was examined. The comparison was made between three kinds of reflector element materials: graphite, beryllium, and beryllium oxide. MCNP5 Monte Carlo computations of the effective neutron multiplication factor ( k ef f ) of the reactor according to the number of reflector material elements inserted in the reactor core for these three reflector elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In these studies, the coolant was light water. Also from this model, Abdelaziz Darif et al [8] calculated the dependence of the effective neutron multiplication factor (k eff ) on the number of reflectors in the core of the reactor. The results showed that keff can be increased without changing the size of the core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the coolant was light water. Also from this model, Abdelaziz Darif et al [8] calculated the dependence of the effective neutron multiplication factor (k eff ) on the number of reflectors in the core of the reactor. The results showed that keff can be increased without changing the size of the core.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there are not many studies on neutron parameters for ADSR using molten Pb-Bi as a target and coolant. In this paper, ADSR was simulated based on TRIGA-Mark II reactor structure [6][7][8] using the MCNPX program. From this structure, the neutron parameters were calculated, including:…”
Section: Introductionmentioning
confidence: 99%